2018
DOI: 10.1186/s12944-017-0646-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistently high psychological well-being predicts better HDL cholesterol and triglyceride levels: findings from the midlife in the U.S. (MIDUS) longitudinal study

Abstract: BackgroundPsychological correlates of blood lipid levels have been previously evaluated mostly in cross sectional studies. However, prospectively measured psychological factors might also predict favorable blood lipid profiles, thereby indicating a healthy mind/body interplay that is associated with less disease, better health and longer lives.MethodsThis paper examined whether longitudinal profiles of psychological well-being over 9–10 years are predictors of blood lipid profiles. Using the MIDUS (Midlife in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
103
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 56 publications
9
103
0
Order By: Relevance
“…The second block includes five studies focused on studying the differential responses of obese and non-obese subjects to dietary challenges (Table 2 ) (Badoud et al 2015b ; Baker et al 2015 ; Geidenstam et al 2014 ; Bak et al 2018 ). The third block comprises three studies that used metabolomics to predict weight loss (Geidenstam et al 2017a , b ; Stroeve et al 2016 ) and 11 randomized clinical trials (RCTs) aimed to assess the effects of weight loss interventions (both hypocaloric diet programs and exercise interventions) on the metabolomic profiles of overweight or obese human subjects (Table 2 ) (Almanza-Aguilera et al 2018 ; Duft et al 2017 ; Kang et al 2018 ; Leal-Witt et al 2018 ; Meucci et al 2017 ; Mills et al 2019 ; Munukka et al 2018 ; Palau-Rodriguez et al 2019 ; Perez-Cornago et al 2014 ; Zheng et al 2016a , b ). Additionally, the fourth block includes 11 articles that studied the effects of specific dietary patterns or dietary compounds on obesity-related metabolic alterations in humans, such as inflammation or oxidative stress (Table 3 ) (Baldrick et al 2018 ; Gu et al 2013 ; Hernández-Alonso et al 2019 ; Hibberd et al 2019 ; Kim et al 2013 ; Kim et al 2017 ; Mayengbam et al 2019 ; Nieman et al 2012a , b ; Romo-Hualde et al 2018 ; Xu et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second block includes five studies focused on studying the differential responses of obese and non-obese subjects to dietary challenges (Table 2 ) (Badoud et al 2015b ; Baker et al 2015 ; Geidenstam et al 2014 ; Bak et al 2018 ). The third block comprises three studies that used metabolomics to predict weight loss (Geidenstam et al 2017a , b ; Stroeve et al 2016 ) and 11 randomized clinical trials (RCTs) aimed to assess the effects of weight loss interventions (both hypocaloric diet programs and exercise interventions) on the metabolomic profiles of overweight or obese human subjects (Table 2 ) (Almanza-Aguilera et al 2018 ; Duft et al 2017 ; Kang et al 2018 ; Leal-Witt et al 2018 ; Meucci et al 2017 ; Mills et al 2019 ; Munukka et al 2018 ; Palau-Rodriguez et al 2019 ; Perez-Cornago et al 2014 ; Zheng et al 2016a , b ). Additionally, the fourth block includes 11 articles that studied the effects of specific dietary patterns or dietary compounds on obesity-related metabolic alterations in humans, such as inflammation or oxidative stress (Table 3 ) (Baldrick et al 2018 ; Gu et al 2013 ; Hernández-Alonso et al 2019 ; Hibberd et al 2019 ; Kim et al 2013 ; Kim et al 2017 ; Mayengbam et al 2019 ; Nieman et al 2012a , b ; Romo-Hualde et al 2018 ; Xu et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles (Leal-Witt et al 2018 ; Kang et al 2018 ; Palau-Rodriguez et al 2019 ; Mills et al 2019 ; Almanza-Aguilera et al 2018 ; Perez-Cornago et al 2014 ; Zheng et al 2016a , b ) focused on determining the effect of weight loss on the metabolomics profiles of overweight and obese individuals. The article from Zheng et al ( 2016b ) was approached as two studies because the study design including two different cohorts, see below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the findings are based on single-sourced, selfreported measures of health. Although prior studies have shown that self-reported health including subjective health and chronic conditions are valid indicators of physical health (e.g., Bound, 1989;Idler and Benyamini, 1997;Miilunpalo et al, 1997), future research should examine whether the effects can be expanded to objective measures of health from multiple sources (e.g., Radler et al, 2018). Moreover, the current study used longitudinal data only measured at two time points, which did not allow other statistical methods that classify longitudinal profiles of continuous variables with more precision (e.g., latent transition analysis).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is unknown whether distinct aspects of well-being benefit health in different cultural contexts. To address this issue, the current study examined longitudinal links between diverse indicators of well-being and self-reported health in Japan, using assessments comparable to a prior study in the United States (Ryff et al, 2015;Radler et al, 2018). Japan is a relevant comparison because it is comparable to advanced Western countries in modern lifestyles and economic development, but also encompasses substantial differences in conceptions of self and relationships with others (Markus and Kitayama, 1991).…”
Section: Introductionmentioning
confidence: 99%